WEBVTT
00:00:01.030 --> 00:00:12.010
Find the number of geometric means inserted between 82 and 1,312 given the sum of the last two means equals twice the sum of the first two means.
00:00:13.340 --> 00:00:24.710
If we know that geometric means have been inserted between 82 and 1,312, then 82 and 1,312 are part of a geometric sequence.
00:00:25.370 --> 00:00:30.780
We can identify 82 as the first term in the sequence, π sub one.
00:00:31.590 --> 00:00:38.220
We know that 1,312 is the final term in the sequence, but we donβt know how many terms there are.
00:00:38.430 --> 00:00:40.740
So weβll label it as π sub π.
00:00:41.510 --> 00:00:54.880
The general term of a geometric sequence with the first term π sub one and a ratio of π is π sub π equals π sub one times π to the π minus one power.
00:00:56.750 --> 00:01:09.580
This means we can write the equation π sub π minus two plus π sub π minus one equals two times π sub two plus π sub three.
00:01:10.650 --> 00:01:22.080
The left side of our equation, it represents the sum of the last two means, and the right side we have two times the sum of the first two means.
00:01:23.160 --> 00:01:29.940
We want to rewrite all of these values in terms of π sub one and π.
00:01:30.750 --> 00:01:41.700
π sub two, thatβs the first mean after our initial value, is equal to 82 times π to the two minus one power.
00:01:42.450 --> 00:01:44.800
And π to the first power is just π.
00:01:46.690 --> 00:01:51.460
The second mean in the sequence would be 82 times π squared.
00:01:52.480 --> 00:01:56.730
π sub π minus two is a little bit more difficult to find.
00:01:57.030 --> 00:02:08.450
Itβs equal to 82 times π to the π minus two minus one power, which simplifies to 82 times π to the π minus three power.
00:02:09.230 --> 00:02:16.310
And then π sub π minus one equals 82 times π to the π minus two power.
00:02:17.410 --> 00:02:21.240
Then we plug these values back into the equation that we initially wrote.
00:02:22.080 --> 00:02:28.450
On the left, we can factor out the term 82 times π to the π minus three power.
00:02:29.400 --> 00:02:37.920
Remember the power rule that tells us π to the π₯-power times π to the π¦-power equals π to the π₯ plus π¦ power.
00:02:38.620 --> 00:02:47.480
If you multiply 82 times π to the π minus three power times π, youβre multiplying by π to the first power.
00:02:47.960 --> 00:02:52.140
And π minus three plus one equals π minus two.
00:02:53.060 --> 00:03:01.260
This is what happens when we take out a factor of π to the π minus three power from π to the π minus two power.
00:03:02.330 --> 00:03:05.700
On the right-hand side, the factoring is a little bit easier.
00:03:06.040 --> 00:03:10.780
We take out a term of 82π, and that leaves us with one plus π.
00:03:11.630 --> 00:03:14.970
Remember that our π-value is a ratio.
00:03:15.940 --> 00:03:24.170
And if you have a negative ratio in your geometric sequence, then the terms will alternate negative, positive, negative, positive.
00:03:25.020 --> 00:03:36.530
We can eliminate negative one as an option for our π as that would make the geometric sequence 82, negative 82, 82, negative 82, and so on.
00:03:37.810 --> 00:03:48.900
If we divide through by one plus π on both sides, weβll end up with 82π to the π minus three power equals 164π.
00:03:49.660 --> 00:03:54.260
We have the 164 because weβve multiplied 82 by two on the right side.
00:03:55.120 --> 00:04:00.110
From there, we can divide both sides of the equation by 82π to the first power.
00:04:00.940 --> 00:04:09.150
Again, weβll remember a power rule π to the π₯-power over π to the π¦-power equals π to the π₯ minus π¦ power.
00:04:10.160 --> 00:04:26.760
On the left, weβll have 82 divided by 82 equals one, and π to the π minus three power divided by π becomes π to the π minus four power, and on the right, 164π divided by 82π equals two.
00:04:27.650 --> 00:04:30.640
At this point, we have an equation with two unknowns.
00:04:30.670 --> 00:04:34.200
And this means to solve, weβll need another equation.
00:04:34.780 --> 00:04:39.490
We know what π sub π equals, 1,312.
00:04:40.200 --> 00:04:46.950
We also know that π sub π can be rewritten as 82 times π to the π minus one power.
00:04:47.490 --> 00:04:58.030
If we plug in 1,312 here and then divide both sides by 82, we get 16 equals π to the π minus one power.
00:04:58.610 --> 00:05:06.910
What we wanna try to do now is rewrite π to the π minus four power in terms of π to the π minus one power.
00:05:07.870 --> 00:05:17.760
We can do that by saying π to the π minus one power times π to the negative three power, again using our power rules.
00:05:18.390 --> 00:05:22.270
We know that π to the π minus one power equals 16.
00:05:22.570 --> 00:05:25.390
So we can substitute 16 in here.
00:05:25.930 --> 00:05:28.940
How do we deal with this π to the negative three power?
00:05:29.590 --> 00:05:32.540
We can rearrange this, but itβll take a few steps.
00:05:33.440 --> 00:05:38.300
First, we rewrite π to the negative three power as one over π cubed.
00:05:39.150 --> 00:05:44.230
From there, we multiply both sides of the equation by π cubed and then divide by two.
00:05:44.690 --> 00:05:46.920
We have eight equals π cubed.
00:05:47.560 --> 00:05:52.940
The cube root of eight is two, and the cube root of π cubed equals π.
00:05:53.820 --> 00:05:59.330
Remember that π-variable represents the ratio in this geometric sequence.
00:06:00.110 --> 00:06:07.070
This means the second term in the sequence will be 82 times two, 164.
00:06:07.760 --> 00:06:13.080
The third term will be 164 times two, 328.
00:06:14.220 --> 00:06:16.810
The fourth term will be 656.
00:06:17.580 --> 00:06:22.450
And 656 times two equals 1,312.
00:06:23.110 --> 00:06:28.500
This means that we know our π sub π is π sub five.
00:06:29.420 --> 00:06:34.430
1,312 is the last term in the sequence, and itβs the fifth term.
00:06:35.310 --> 00:06:52.530
But when we count the geometric means, we do not count the first term or the last term, as these are not means, which means the number of geometric means inserted between 82 and 1,312 under these conditions is three.